PEMBELAJARANBERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA SMP - Herman, Tatang (Jurnal Cakrawala Pendidikan, 2007)
_ .... JI..\\..Il'-'.llAII,A,.ll learning of mathematics, generally learners...... _Jl..Jl..Jl..lI,A..... JI.. ...........' ....... to ask questions and argunlents throug11a process in-group negotiation, and reflection so thatthey could formulate conjectures and conclusions.collaborative research conducted throughproblem-based and focused onmathematical reasoning ability of junior high school-.'L' .....· .......... _' ...... U ...ALLJI ...... _ .......:J were forty-six students of Grade 2BBandung, a state junior higl1 school. Thethe research were tests on reasoning ability,sheets, students' diaries/journals, andresearch results indicate that the learning